2013
DOI: 10.5020/18061230.2013.p381
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de dismenorreia em universitárias e sua relação com absenteísmo escolar, exercício físico e uso de medicamentos

Abstract: Prevalence of dysmenorrhea in university students and its relation to school absenteism, physical exercise and use of medicinesPrevalencia de dismenorrea en universitarias y su relación con absentismo escolar, actividad física y uso de medicamentos RESUMO Objetivo: Verificar a prevalência de dismenorreia em universitárias e a frequência de absenteísmo escolar, prática de exercícios físicos e utilização de medicamentos para tratamento dessa síndrome. Métodos: Trata-se de um estudo transversal realizado com jove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
0
0
12
Order By: Relevance
“…According to the results, over half of the nursing students suffered from moderate dysmenorrhoea, while about a quarter suffered from severe dysmenorrhoea and only a few complained of mild dysmenorrhoea. This is consistent with other studies, which found that more than half of their participants had moderate pain [9,10]. In contrast, however, two cross-sectional studies in Saudi Arabia found that the majority of their respondents complained of severe dysmenorrhoea [5,11].…”
Section: Discussionsupporting
confidence: 88%
“…According to the results, over half of the nursing students suffered from moderate dysmenorrhoea, while about a quarter suffered from severe dysmenorrhoea and only a few complained of mild dysmenorrhoea. This is consistent with other studies, which found that more than half of their participants had moderate pain [9,10]. In contrast, however, two cross-sectional studies in Saudi Arabia found that the majority of their respondents complained of severe dysmenorrhoea [5,11].…”
Section: Discussionsupporting
confidence: 88%
“…Ecossistemas marinhos 37 Ensino de Biologia 20,22 Epistemología 57,58,61,62,63,64,66,67,68 F Fungi 1,9 Fungo parasita 4…”
Section: íNdice Remissivounclassified
“…A DP contribui com a ausência das mulheres no ambiente de trabalho e no âmbito escolar, onde um terço da população feminina e cerca de 5 a 14% desta população possuem absenteísmos frequentes, resultando em consequências negativas sobre a saúde e as condições relacionadas à qualidade de vida, afetando a produtividade em decorrência as faltas ao trabalho frequente, e em curto prazo e declínio do rendimento escolar (7)(8)(9)(10) .…”
Section: Introductionunclassified
“…A dor é do tipo espasmódica e ocorre 1 a 3 dias antes do período menstrual. (Nunes et al, 2013). A prevalência da dismenorreia é maior em adolescentes, entretanto ela pode se manifestar em qualquer faixa etária dentre as mulheres em idade fértil.…”
Section: Introductionunclassified